Pengaruh Kombinasi Polimer Polivinil Pirolidon dan Etil Selulosa terhadap Karakteristik dan Uji Penetrasi Formulasi Transdermal Patch Ekstrak Bawang Dayak (Eleutherine palmifolia (L) - Novia Novia; Noval Noval (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2021)
The transdermal patch can deliver the active substance with good bioavailability, then made formulations of such preparations from dayak onion extract, which has a compound content of flavonoids, with a combination of polymer PVP K30 and ethyl cellulose to produce transdermal patches with good physical evaluation and penetration. The research aims to carry out the effect and ideal formulation of transdermal patches of dayak onion extract with a combination of polymers PVP K30 and ethyl cellulose based on physical evaluation and penetration—manufacture of transdermal patches using the solvent evaporation method. Physical evaluation includes organoleptic testing, weight uniformity, thickness, folding resistance, and moisture testing. Then evaluate the penetration of the active substance using Franz diffusion cells. Analyze data with One Way ANOVA. The physical evaluation results of weight uniformity, patch thickness, folding resistance, and moisture test of transdermal patches on F1, F2, F3, and F4 meet the requirements. As for the results of penetration tests, F1, F2, F3, and F4 can be penetrated from 120 minutes to 180 minutes with the concentration of active substances that are linearly penetrated. The combination of polymers PVP K30 and ethylcellulose has affected the physical evaluation of transdermal patches of dayak onion extract. Based on the physical evaluation and penetration test in vitro obtained, the most optimal formula results are F3 with comparison PVP K30 and ethyl cellulose (100:300).